Two Armies on the Rio Grande : The First Campaign of the US-Mexican War - Murphy, Douglas A. (Book collections on Project MUSE., 2014)
The opening campaign of the US-Mexican War transformed the map of each nation and shaped the course of conflict. Armed with a broad range of Mexican military documents and previously unknown US sources, Douglas Murphy provides the first balanced view of early battles such as Palo Alto and Resaca de la Palma. He reassesses previously covered territory and also poses new questions. Why did Mexico establish its defenses south of the Rio Grande while claiming territory north of the river? What was Mexico's strategy in the campaign against the United States? What factors most affected Mexico's defeat.